2004
DOI: 10.1016/s0896-6273(04)00085-6
|View full text |Cite
|
Sign up to set email alerts
|

A Cacna1a Knockin Migraine Mouse Model with Increased Susceptibility to Cortical Spreading Depression

Abstract: Migraine is a common, disabling, multifactorial, episodic neurovascular disorder of unknown etiology. Familial hemiplegic migraine type 1 (FHM-1) is a Mendelian subtype of migraine with aura that is caused by missense mutations in the CACNA1A gene that encodes the alpha(1) subunit of neuronal Ca(v)2.1 Ca(2+) channels. We generated a knockin mouse model carrying the human pure FHM-1 R192Q mutation and found multiple gain-of-function effects. These include increased Ca(v)2.1 current density in cerebellar neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

34
555
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 602 publications
(593 citation statements)
references
References 45 publications
34
555
1
3
Order By: Relevance
“…31,35 Accordingly, at low voltages close to the threshold of activation of mutant channels, the gainof-function of the Ca V 2.1 current was larger in S218L KI mice than in R192Q KI mice. 39,41 The changes in whole-cell Ca V 2.1 current density in neurons from knockin mice were very similar to the changes in single channel Ca 2ϩ influx of mutant recombinant human Ca V 2.1 channels, indicating that FHM1 mutations produce a similar gain-of-function of Ca 2ϩ influx through mouse and human Ca 2ϩ channels. The analysis of mutant channels in neurons of knockin mice revealed that FHM1 mutations produce gain of function of Ca V 2.1 channels at both the single channel and wholecell level.…”
Section: Familial Hemiplegic Migraine Type 1 (Fhm1)mentioning
confidence: 83%
See 3 more Smart Citations
“…31,35 Accordingly, at low voltages close to the threshold of activation of mutant channels, the gainof-function of the Ca V 2.1 current was larger in S218L KI mice than in R192Q KI mice. 39,41 The changes in whole-cell Ca V 2.1 current density in neurons from knockin mice were very similar to the changes in single channel Ca 2ϩ influx of mutant recombinant human Ca V 2.1 channels, indicating that FHM1 mutations produce a similar gain-of-function of Ca 2ϩ influx through mouse and human Ca 2ϩ channels. The analysis of mutant channels in neurons of knockin mice revealed that FHM1 mutations produce gain of function of Ca V 2.1 channels at both the single channel and wholecell level.…”
Section: Familial Hemiplegic Migraine Type 1 (Fhm1)mentioning
confidence: 83%
“…[39][40][41] The studies in heterologous expression systems showed that the FHM1 mutations alter many biophysical properties of human Ca V 2.1 channels, in a complex way. In some cases (e.g., in the case of the channel inactivation properties) the effects were different depending on the mutation.…”
Section: Familial Hemiplegic Migraine Type 1 (Fhm1)mentioning
confidence: 99%
See 2 more Smart Citations
“…These results indicate that the excitability of the cerebral cortex might be increased by chronic dysfunction of serotonergic innervation in the cerebral cortex, and such a mechanism would explain the facilitation of migraine with a low serotonin disposition. Likewise, increased excitability of the cerebral cortex caused by gene mutation, such as missense mutation of CACNA1A (encoding the α 1 subunit of neuronal Cav2.1(P/Q-type) calcium channels), a representative gene mutation in familial hemiplegic migraine (FHM) families, induces migraine susceptibility by lowering the threshold of cortical SD generation [55] . …”
mentioning
confidence: 99%